Liberating Reason From the Passions - Feinberg, Matthew; Willer, Robb; Antonenko, Olga; John, Oliver P. (Psychological Science, 2012)
A classic problem in moral psychology concerns whether and when moral judgments are driven by intuition versus deliberate reasoning. In this investigation, we explored the role of reappraisal, an emotion-regulation strategy that involves construing an emotion-eliciting situation in a way that diminishes the intensity of the emotional experience. We hypothesized that although emotional reactions evoke initial moral intuitions, reappraisal weakens the influence of these intuitions, leading to more deliberative moral judgments. Three studies of moral judgments in emotionally evocative, disgust-eliciting moral dilemmas supported our hypothesis. A greater tendency to reappraise was related to fewer intuition-based judgments (Study 1). Content analysis of open-ended descriptions of moral-reasoning processes revealed that reappraisal was associated with longer time spent in deliberation and with fewer intuitionist moral judgments (Study 2). Finally, in comparison with participants who simply watched an emotion-inducing film, participants who had been instructed to reappraise their reactions while watching the film subsequently reported less intense emotional reactions to moral dilemmas, and these dampened reactions led, in turn, to fewer intuitionist moral judgments (Study 3).